Mac OS X Black Book. - Bell, Mark R.; Suggs, Deborah; Steinberg, Gene (Little Black Books (Coriolis) Ser., 2001)
Annotation This book goes way beyond the basics with technical references and practical troubleshooting, administrative tools, networking technologies, and more. It is especially designed to get to the heart of networking issues for systems administrators who want to include Mac OS in Windows or Unix environments. It shows readers how to automate tasks remotely over TCP/IP using Applescript. Covers support for symmetric multiprocessing and Carbon.